Protein and Lipid Compositions of Isolated Plasma Membranes from Orchard Grass (Dactylis glomerata L.) and Changes during Cold Acclimation - Yoshida, Shizuo (1984)
The chemical composition of plasma membrane fractions isolated from orchard grass seedlings (Dactylis glomerata L.) was analyzed and compared with endomembranes. The plasma membrane is characterized by an enrichment of sterols and a lower degree of unsaturation of phospholipids. Steryl glycosides were found to be one of the lipid components of the plasma membrane, but steryl esters and galactolipids were barely detectable. Diphosphatidyl glycerol was characteristically detected in the mitochondrial membrane, but not in the plasma membrane fraction. Plasma mambrane fraction was also characterized by its `lower fluidity' in comparison with the endomembranes. This may be due to the large amount of sterols and the lower degree of phospholipid unsaturation in plasma membranes. Electrophoretic comparison of polypeptides was also made between different membranes. The distribution patterns of polypeptides revealed on one- and two-dimensional SDS-slab gels were characteristic for those membranes. The presence of glycopeptide complements was a useful criterion for distinguishing plasma membrane from other membranes. The plasma membrane and the ER + Golgi membranes were enriched in glycopeptides. However, a marked difference was revealed in the total number and the molecular weights of the peptides. During cold acclimation of orchard grass seedlings, the degree of fatty acid unsaturation increased only slightly in plasma membrane, unlike in endomembranes. The change in sterols-to-phospholipids ratio in plasma membrane was also slight. On the other hand, the phospholipid-to-protein ratio increased significantly in the plasma membrane as cold hardiness increased. A significant change in the polypeptide complements of plasma membrane was also demonstrated during cold acclimation.